2020
DOI: 10.3390/molecules25112580
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Different Approaches to Quantify Nitric Oxide Release from NO-Releasing Materials in Relevant Biological Media

Abstract: The development of solid materials that deliver nitric oxide (NO) are of interest for several therapeutic applications. Nevertheless, due to NO’s reactive nature, rapid diffusion and short half-life, reporting their NO delivery characteristics is rather complex. The full knowledge of this parameter is fundamental to discuss the therapeutic utility of these materials, and thus, the NO quantification strategy must be carefully considered according to the NO-releasing scaffold type, to the expected NO-releasing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…Although several more sensitive techniques can be used to measure nitrite, including fluorometric, electrochemical, and 3-nitrotyrosine quantification assays [32], the classical Griess spectrophotometric assay is most frequently used. In this experimental in vitro model of inflammation, NO levels reached 0.6-34 µM in the culture medium and these values are within the detection range of the Griess reaction [33]. Our results demonstrate that ω3-PC and ω6-PC inhibit the lipopolysaccharide-stimulated production of nitric oxide.…”
Section: Discussionsupporting
confidence: 73%
“…Although several more sensitive techniques can be used to measure nitrite, including fluorometric, electrochemical, and 3-nitrotyrosine quantification assays [32], the classical Griess spectrophotometric assay is most frequently used. In this experimental in vitro model of inflammation, NO levels reached 0.6-34 µM in the culture medium and these values are within the detection range of the Griess reaction [33]. Our results demonstrate that ω3-PC and ω6-PC inhibit the lipopolysaccharide-stimulated production of nitric oxide.…”
Section: Discussionsupporting
confidence: 73%
“…Previous studies have already demonstrated the high affinity of Zeolite 4A for NO and H 2 S adsorption, being the main reason for using this carrier in the present work. 19,23,24 After degassing, most of the water molecules are removed from the zeolite cavities, allowing the gas to diffuse through the pores and access the metal sites where NO or H 2 S is chemically adsorbed to these metal centers. As the hybrid compound presented a reduced thermal stability (Figure 2B) compared with the zeolite itself, the activation temperature for these materials was set to be 150 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Examples of such materials include zeolites, titanosilicates, clays, and metal–organic frameworks, with storing capacities ranging from ca. 1 to 7 mmol of gas per g of material, covering a wide range of therapeutic needs. , Zeolites are particularly interesting carriers due to their easy commercial access, chemical stability, and biocompatibility features, being used for decades in drug delivery. , Zeolite A, a three-dimensional nanoporous crystalline aluminosilicate, is within the few porous materials that demonstrate the ability to adsorb therapeutic amounts of either NO or H 2 S. ,, Moreover, this zeolite offers a great advantage to be easily modified by ion exchange, being possible to achieve different release profiles by tailoring the type and number of metal cations present in the framework. , However, due to their high affinity to water, zeolites present a quick NO/H 2 S release when in contact with biological solutions and the ion-exchanged configurations are not stable enough in aqueous media, releasing the metals along with the gas in the therapeutic tissues, compromising their efficient delivery and inducing cell toxicity. ,, …”
Section: Introductionmentioning
confidence: 99%
“…A validated enzyme-linked immunosorbent assay (ELISA) reader (Sunrise, Tecan, Austria) was then used to measure absorbance at 540 nm. Serum NOx concentration was determined as a deviation from the linear standard curve at a scale from 0 to 100 μM sodium [ 9 ].…”
Section: Methodsmentioning
confidence: 99%